GE_GERICHTE P/20105/2017 vom 31. Januar 2019 - GE Cour de justice (2019)
NE BIS IN IDEM ; PLAINTE PÉNALE ; RETRAIT(VOIE DE DROIT) ; INFRACTIONS CONTRE LE PATRIMOINE | CPP.115; CPP.310; CP.120; CP.33.al4; CPP.11.al1; CPP.11.al2; CPP.323